Determination of the interface state density of the In/p-Si Schottky diode by conductance and capacitance-frequency characteristics - Tugluoglu, N.; Yakuphanoğlu, Fahrettin; Karadeniz, S. (Elsevier Science Bv, 2007)
The electrical characterization of the In/p-Si Schottky diode has been investigated by conductance and capacitance-frequency techniques. The characteristic parameters of the interface states have been determined from the capacitance-frequency and conductance-frequency measurements. The capacitance of the In/p-Si Schottky diode decreases with increasing frequency. The increase in capacitance at lower frequencies results from the presence of interface states. The peak observed in the conductance curve of the In/p-Si diode indicates the presence of an interfacial layer in the In/p-Si Schottky barrier. The interface-state parameters, interface-state density D-it and relaxation time tau of the In/p-Si diode were calculated. The interface-state density was found to vary from 7.82 x 10(12) eV(-1) cm(-2) in (0.53-E-v)eV to 8.01 x 10(12) eV(-1) cm(-2) in (0.28-E-v)eV. Furthermore, the relaxation time was found to vary from 4.543 x 10(-8) s in (0.53-E-v) eV to 4.435 x 10(-8) s in (0.28-E-v) eV. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Schottky diode; interface state density; conductance